Thermodynamic analysis of combined cycle plant operation as part of an energy-saving system based on an absorption bromide-lithium refrigerating machine - L. V. Galimova; D. Z. Bairamov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The main directions of research of the current energy-generating system, taking into account its technical limitations, are optimization and forecasting based on the analysis of its operating modes. Thermodynamic analysis involves determining the efficiency of the system based on the research of exergy efficiency and exergy losses. In this project, we propose methodic and results of exergy analysis of combined cycle gas plant operation as an object of energy production, the efficiency which is provided by cooling the outdoor air using an absorption bromide-lithium refrigerating machine. Conducting exergy analysis for determination of exergy destruction allow to determine the potential for increasing the efficiency of the system. A flow graph and an incident matrix are presented. The exergy efficiency of the combined cycle gas plant under the specified conditions is 46,5%. Based on the exergy analysis, the final diagram of the distribution of fluxes and losses of exergy of the combined cycle gas plant is presented